2013
DOI: 10.1371/journal.pone.0071148
|View full text |Cite
|
Sign up to set email alerts
|

Ancient Dispersal of the Human Fungal Pathogen Cryptococcus gattii from the Amazon Rainforest

Abstract: Over the past two decades, several fungal outbreaks have occurred, including the high-profile ‘Vancouver Island’ and ‘Pacific Northwest’ outbreaks, caused by Cryptococcus gattii, which has affected hundreds of otherwise healthy humans and animals. Over the same time period, C. gattii was the cause of several additional case clusters at localities outside of the tropical and subtropical climate zones where the species normally occurs. In every case, the causative agent belongs to a previously rare genotype of C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
99
0
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 123 publications
(106 citation statements)
references
References 43 publications
6
99
0
1
Order By: Relevance
“…The WGST data showed clearly that the VGIIc genotype responsible for the most recent infections in the Pacific Northwest is genetically distinct from both VGIIa and VGIIb Vancouver Island outbreak subtypes and suggest that all three subtypes are equally distinct from each other (52). Similar findings based on multilocus sequence typing (MLST) and MLMT analyses, which have been confirmed based on WGST, have been reported recently (53)(54)(55). All studies suggest that the three subtypes have arisen as a result of recombination events that took place prior to their introduction into the Pacific Northwest.…”
Section: Phylogenetic Studies and Molecular Subtypingsupporting
confidence: 81%
See 3 more Smart Citations
“…The WGST data showed clearly that the VGIIc genotype responsible for the most recent infections in the Pacific Northwest is genetically distinct from both VGIIa and VGIIb Vancouver Island outbreak subtypes and suggest that all three subtypes are equally distinct from each other (52). Similar findings based on multilocus sequence typing (MLST) and MLMT analyses, which have been confirmed based on WGST, have been reported recently (53)(54)(55). All studies suggest that the three subtypes have arisen as a result of recombination events that took place prior to their introduction into the Pacific Northwest.…”
Section: Phylogenetic Studies and Molecular Subtypingsupporting
confidence: 81%
“…These findings agree with a recent comprehensive, global study of VGII strains, which traced the origin of both outbreak subgenotypes VGIIa and VGIIb back to an ancestral C. gattii strain, LMM645, from the Amazon rainforest. This study revealed the presence of the VGIIa and VGIIb genotypes and MATa and MAT␣ strains in Brazil and showed clear evidence for recombination among the Brazilian C. gattii population (53).…”
Section: Global Distribution and Movement Of C Gattii Genotypesmentioning
confidence: 55%
See 2 more Smart Citations
“…Until recently, evidence was balanced between the likeliest candidates: South America, Africa and Australia (which all had evidence of recombination and genetic diversity). However, recently, the case for South America has strengthened [29], due to the discovery of a strain displaying a basal genetic lineage in virgin Amazonian rainforest, where contamination from imported woods is thought extremely unlikely [84].…”
Section: Vancouver Island Outbreakmentioning
confidence: 99%